Avaliação de diferentes materiais utilizados na composição de filtros quando associados a aplicação de coagulantes no tratamento de água - Vizibelli, Dandley (2019)
The exponential growth of the human population presents as major challenges in the water supply to maintain a production that meets the demand and maintain the necessary quality for this supply. In view of this new studies seek to find alternatives in order to overcome these challenges, achieving a better efficiency throughout the treatment process. This study aims to identify the efficiency of alternative materials such as filter bed composition using a direct downward filtration system in the treatment of water associated with Moringa oleifera and Aluminum sulphate coagulants through treatment processes commonly used in water treatment plants. Four filters were developed, Sand Filter (F1), Coconut Fiber Filter (F2), Needle Geotextile Filter (F3), and Coffee Grounds Filter (F4), and the results were compared by analyzing the pH, temperature, electrical conductivity, apparent color, turbidity, total solids, total coliforms, and Escherichia coli.The temperature parameter did not show great variation during the water treatment procedures, the pH parameter presented variation only in the treatments where the F4 filter was used. Regarding the electrical conductivity parameter, only the treatments where Moringa oleifera coagulant solution was applied showed higher values than the others. With the exception of the Aluminum sulphate/F2 treatment, all the others reached values of turbidity removal efficiency and apparent color removal efficiency above 95%. All treatments showed sufficient total solids removal efficiency so that the final values are in accordance with the legislation. It was not possible to identify efficiency in the removal of fecal coliforms and Escherichia coli that comply with the limits established in legislation since the disinfection process was not analyzed. Among the two coagulants used, the Aluminum sulphate achieved the best results and the filter that presented the best performance was the filter of needle geotextile (F3), and in all treatments where it is used, the parameters remained within the limits established in legislation, except for the microbiological parameters, where again the treatments where the F3 filter was used achieved the best removal results. The treatment of Aluminum sulphate/F3 presented the best set of results, the treatment whose coagulant employee was the Moringa oleifera that presented the best set of results was Moringa oleifera/F3. It is suggested to continue this work in order to improve the filters as to the ideal thickness of the layers of the materials composing the filter bed, and to add the disinfection process to obtain a complete treatment process.